Management of Incidents and Product Withdrawal - Górna , Justyna (Studia Oeconomica Posnaniensia, 2016)
In order to assure food safety, food-processing manufacturers must show initiative in preparation for potential crisis situations. Legal requirements oblige companies to take immediate action when an available product poses a threat to the consumer’s health or life. These actions imply blocking a suspicious batch or a possible product withdrawal from the market, as well as effective communication with supervisory authorities and consumers if a product has already been available to them. The scope of these regulations is scrupulously listed in private safety standards and food quality, such as BRC, IFS, or in the international norm ISO 22000. Effective management of incidents and potential crisis situations requires preparation of a specific procedure. This procedure should identify potential incidents and crisis situations; moreover, it should regulate the rules of specific proceedings in an alert mode. First of all, a key role is played by the crisis team, which makes the decisions in the case of crisis situations. The procedure has to be tested to make sure it guarantees the effectiveness of particular actions. Manufacturers often have problems with creating particular procedures that would simplify decision-making during crisis situations. The aim of this paper is to present the rules of procedure creation, incidents managements and product withdrawal from the market, as well as the guidelines for its testing.